Teorema Titik Tetap Kannan Pada Ruang Modular-2 - Nurnugroho, Burhanudin Arif (Quadratic: Journal of Innovation and Technology in Mathematics and Mathematics Education, 2025)
Kannan's fixed point theorem, constructed initially on metric spaces, has been developed for several abstract spaces. This research will study Kannan's fixed point theorem on 2-modular spaces.